2017
DOI: 10.3892/etm.2017.5410
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b alleviates oxygen and glucose deprivation/reperfusion-induced injury via inhibition of the p53‑dependent apoptosis pathway in N2a neuroblastoma cells

Abstract: Cerebral ischemic injury causes severe brain damage and remains one of the leading causes of morbidity and mortality worldwide. Members of the microRNA-29 (miR-29) family are involved in regulating the process of ischemia and may be developed as biomarkers to diagnose and treat cerebral ischemia. The role of miR-29b in cerebral ischemia injury remains poorly understood. The purpose of the present study was to investigate whether miR-29b overexpression suppressed cerebral ischemic injury and to explore its unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…For example, Zhu et al () constructed the OGD model and probed the protective impacts of ginsenoside Rb3 on OGD‐evoked PC‐12 cell ischemic injury. Cao et al () confirmed the protective impacts of miR‐29b on OGD/R‐evoked cell injury in N2a neuroblastoma cells. Wang et al () discovered that the repression of miR‐142‐5p could alleviate OGD/R‐evoked neuron injury via mediating Nrf2/ARE signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…For example, Zhu et al () constructed the OGD model and probed the protective impacts of ginsenoside Rb3 on OGD‐evoked PC‐12 cell ischemic injury. Cao et al () confirmed the protective impacts of miR‐29b on OGD/R‐evoked cell injury in N2a neuroblastoma cells. Wang et al () discovered that the repression of miR‐142‐5p could alleviate OGD/R‐evoked neuron injury via mediating Nrf2/ARE signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, in vivo and in vitro knock down models of miR-29b demonstrated loss of neuronal viability in spinal cord injury or dorsal root ganglia [76,126], while delivery of a miR-29b-3p -mimic, prohibits chemotherapeutically induced apoptosis in cardiomyocytes through regulation of the mitochondria-dependent apoptotic pathway [117]. The overexpression of miR-29b-3p could alleviate or prevent OGD-induced (oxygen-glucose deprivation) damage [132,133], whereas its loss led to aggravation of the situation [134]. As shown in optic nerves of zebra fish, raised miR-29b-3p level is believed to play a key role in central nerve regeneration by directly aiming filaments of the cytoskeleton [135].…”
Section: Discussionmentioning
confidence: 99%
“…However, this therapy inevitably leads to ischaemia/reperfusion injury (IRI) and its treatment effect is limited. Accumulating evidence shows that apoptosis and death of nerve cells after I/R are the main causes of aggravating brain injury . Therefore, it is important to develop novel therapeutic strategies to treat cerebral IRI.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that apoptosis and death of nerve cells after I/R are the main causes of aggravating brain injury. 4,5 Therefore, it is important to develop novel therapeutic strategies to treat cerebral IRI.…”
Section: Introductionmentioning
confidence: 99%